Najib al-Kilani's novel and the values of leadership among youth in reviving the society - Maming, Pabiyah; Bahjat, Munjid Mustapha (International Islamic University Malaysia, 2019)
Islam gives prominent attention towards youth, thus some Islamic teachings are addressed specifically to them. It is noted that the Quran pointed out to the youth in more than one place, as well as the noble Sunnah.Youth have a prominent and important role to play in developing the society and the nation. Therefore, the success and progress of a society depends heavily on the well-being of its youth. In recognition of this importance, this study aims to analyze the three novels of Naguib al-Kilani which are “Azrā’s Jakarta,” (The virgin of Jakarta) “Allazīna Yaḥtariqūn,” (Those who are burning), and “ʽAmāliqatu al Syimāl.” (The giants of the South). It also aims to highlight the role of the protagonists at both local and global levels in the liberation of the occupied territory from the hand of colonialism and in the reform of a corrupt society. The data are analyzed using content analysis. In these three novels, the roles of young Muslims are demonstrated in the form of leadership values in society. It is clearly shown in the findings of these novels the effective impact in the minds of young Muslims to reform the society as outlined in the Islamic teachings.